Nitric Oxide Negatively Regulates Larval Metamorphosis in Hard-Shelled Mussel (Mytilus coruscus) - Zhu, You-Ting; Zhang, Ya; Liu, Yu-Zhu; Li, Yi-Feng; Yoshida, Asami; Osatomi, Kiyoshi; Yang, Jin-Long; Liang, Xiao (Frontiers in Marine Science, 2020)
Marine invertebrates undergo distinct life cycles and development processes, and some undergo a metamorphic transition from pelagic larvae to benthic juvenile. Previous studies have shown that the second messenger nitric oxide (NO) plays important roles in regulating larval metamorphosis in marine invertebrates. However, this regulatory function is not conserved. Herein, we investigated the regulatory role of NO in larval metamorphosis in hard-shelled mussel (Mytilus coruscus). Pharmacological experiments revealed that after exposure to nitric oxide synthase (NOS) inhibitors, the larval metamorphosis rate was increased significantly. By contrast, exposure to NO donors significantly reduced the larval metamorphosis rate. To further investigate the function of NO in metamorphosis, we cloned the NOS cDNA sequence from M. coruscus (McNOS), analyzed amino acid sequences of McNOS from different species, and measured McNOS mRNA temporal expression alongside the molecular chaperone heat shock protein 90 (HSP90) in different larval stages. The results showed that NOS proteins share a highly conserved domain sequence in different species, even in invertebrates and vertebrates, but their classification among invertebrates and vertebrates is not the same. Except for the umbo veliger stage, McNOS mRNA was expressed at low levels in pediveliger larval and postlarvae stage, indicating a potential inhibitory function for NO in larval metamorphosis. Meanwhile, HSP90 mRNA expression was correspondingly high in the umbo veliger stage and lower in the pediveliger larval and postlarvae stage, indicating potential functional synergism. Interestingly, McNOS enzyme activity in different larval stages was inconsistent with its mRNA expression. Metamorphosis assays of pharmacological treatments combined with McNOS and HSP90 gene expression and NOS enzyme activity analyses indicated that NO acts as a suppressor to regulate metamorphosis in M. coruscus, regardless of whether NO is endogenous or exogenous.